Giải câu 13 bài ôn tập chương 3: Dãy số, cấp số cộng và cấp số nhân.

Ta phải chứng minh: \({1 \over {b + c}} + {1 \over {a + b}} = {2 \over {c + a}}\)

Biến đổi ta có:

\({1 \over {b + c}} + {1 \over {a + b}} = {2 \over {c + a}}\)

\(\Leftrightarrow {1 \over {b + c}} - {1 \over {c + a}} = {1 \over {c + a}} - {1 \over {a + b}}\)

\(\Leftrightarrow {{c + a - b - c} \over {(c + a)(b + c)}} = {{a + b - c - a} \over {(c + a)(a + b)}}\)

\(\Leftrightarrow {{a - b} \over {b + c}} = {{b - c} \over {a + b}}\)

\(\Leftrightarrow {a^2} - {b^2} = {b^2} - {c^2}\)

$\Leftrightarrow {a^2} + {c^2} = 2{b^2}$

Vậy \({1 \over {b + c}} + {1 \over {a + b}} = {2 \over {c + a}}\)đúng vì \(a^2,b^2,c^2\) lập thành cấp số cộng.

Vậy \({1 \over {b + c}},{1 \over {c + a}};{1 \over {a + b}}\) là cấp số cộng.